INTERNATIONAL STANDARDS AND CRITERIA FOR ECONOMIC SECURITY AS THE BASIS OF ITS MONITORING (International Journal of Innovative Technologies in Economy, 2020)
The article examines the existing international standards and criteria of economic security as a basis for its monitoring. It shows that the processes of guaranteeing economic security are urgent in the modern world and include a significant number of procedures. The vast majority of national security strategies implement economic security through radical economic reforms, integration into world security systems, accession to economic unions and organizations. The study proved that the approaches to the criteria of economic security, the use of standards that determine the level of implementation of economic security, indicates the lack of uniform approaches to the tools for monitoring key indicators of resilience to crises and risks of the economic sphere. The author concluded that macroeconomic indicators are considered as indicators that determine the achievement of economic security; indicators of socio-economic status, functional and sectoral level; indicators of international indices that reflect the economic activity of countries. Along with this, it is advisable to improve the methodology for monitoring the implementation of economic security on the basis of an integrated combination of a set of standards and criteria of economic orientation, which will form a system of effective response to economic risks and crises.